Helminth Parasitism in Isloated Populations of a Neotropical Forest Rodent - Ireland, Annette L. (My University, 2012)
Parasitism is an extremely common life style that has evolved independently many times, and parasites are diverse with respect to that life style. Parasitic nematodes are commonly found in rodents and can serve as excellent model systems for understanding parasite-host interactions. Proechimys semispinosus (the Central American spiny rat) is a widely-distributed and common rodent in Neotropical forests. Several species of intestinal nematodes have been isolated from this rat, including Heligmostrongylus sp. I analyzed data collected from isolated populations of P. semispinosus. The data set included counts of eggs of Heligmostrongylus sp. that were shed in the feces of their rat hosts. The data were collected over a 13-month period (January 1997 through January 1998) from rat populations on seven small islands in Gatun Lake, central Panama. Rats were censused monthly by live trapping, and monthly fruit availability was assessed by counting the numbers of trees and lianas that were producing ripe fruits. Rat populations on five islands were provisioned with supplemental food during the period of least food availability (November and December 1997 and January 1998) to test the effects of host nutritional status on reproductive activity of Heligmostrongylus sp. Rat fecal samples were collected from each captured individual, and nematode eggs were counted from each sample. I estimated monthly rat densities, fruit densities, and per capita fruit availability for each island. I also calculated three indices (egg density, prevalence, and egg density of egg-shedding individuals ) of Heligmostrongylus sp. reproductive activity. Egg density and density of egg-shedding individuals were log10+1-transformed, and prevalence was arcsine square roottransformed. I computed cross-correlation functions of each pair-wise island combination to search for synchrony in nematode reproductive activity among insular populations of rats. I computed Spearman rank correlation coefficients of island-wide means of the three Heligmostrongylus sp. indices and rat density, fruit density, and per capita fruit availability. I used repeated measures analysis of variance (ANOVA) to search for differences in mean parasite indices with respect to treatment period, treatment group, population nested within treatment group, month, and the month x treatment group interaction. I then searched for differences in the mean number of eggs shed by rats according to age and sex by constructing a full ANOVA model that included age, sex, and the interaction. I compared the proportions of male and female rats that shed nematode eggs at some time in their capture histories. I used linear regression analysis to search for a relationship between the number of eggs shed and rat body weight. Reproductive activity of Heligmostrongylus sp. varied widely over time, but there was little evidence of synchrony among islands. There were no associations of the parasite indices with rat density, fruit density, or per capita fruit availability. Food provisioning had no effect on reproductive activity, but such activity varied among islands. There 2 were no differences in Heligmostrongylus sp. reproductive activity between age classes of rats, but female rats shed more eggs than did males. By contrast, the proportions of male and female rats shedding eggs did not differ, and there was no relationship between the number of eggs shed by a rat and it body weight. Results suggest that reproductive activity of Heligmostrongylus sp.is infrequent and aseasonal but spatially variable. Host nutritional status has little effect on nematode reproductive activity, but dietary or physiological consequences of female rat reproduction may increase nematode activity. I suggest that Heligmostrongylus sp. has little impact on host fitness or population-level processes.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science - Biology
Keywords: Rodent population - Panama; Proechimys; Parasites; Parasitism; Helminth